Social support in university music students' coping with performance anxiety: people, strategies and performance situations. (1st January 2022) - Huang, Wei-Lin; Yu, Hui
ABSTRACT: This paper moves beyond a therapeutic perspective in the study of musical performance anxiety (MPA) coping and adopts a social support analytical approach. It explores the collaborative nature of university music students' MPA coping throughout instrumental/vocal learning and performance preparation. Semi-structured interviews and thematic analysis were carried out with 53 undergraduates from a university's music department in the local context of Taiwan. The findings identify that one-to-one tuition teachers provide multifunctional strategies embedded in pedagogical practices, while peers provide emotional support and peer learning, and accompanists act as critical friends. Among the eight MPA coping strategies, contrived performance situation is commonly used while the rests are relevant to certain facilitators: mental and visual rehearsal, accepting mistakes, relaxation skills, and dietary (teacher); absorbing activities and physical activities (peers); and virtual tools (accompanists). With social support, most participants have reported an improvement in their overall performance ability, including both performance skills and MPA coping skills.